2013
DOI: 10.1111/1574-6968.12283
|View full text |Cite
|
Sign up to set email alerts
|

Degradative plasmids from sphingomonads

Abstract: Large plasmids ('megaplasmids') are commonly found in members of the Alphaproteobacterial family Sphingomonadaceae ('sphingomonads'). These plasmids contribute to the extraordinary catabolic flexibility of this group of organisms, which degrade a broad range of recalcitrant xenobiotic compounds. The genomes of several sphingomonads have been sequenced during the last years. In the course of these studies, also the sequences of several plasmids have been determined. The analysis of the published information and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…An example is the genes for the upper and lower pathways of naphthalene of several pseudomonads and sphingomonads (Yen et al, 1988), which are borne on iso-functional nah-plasmids, are often found either on different replicons or are at least organized in several transcriptional units (Stolz, 2009). Moreover, after transfer, these plasmids often undergo evident rearrangements between the various sphingomonads (Basta et al, 2005(Basta et al, , 2004Stolz, 2014). The transfer, maintenance, and recombination of these plasmids, therefore, are of great significance for the exceptional degradative capabilities of this group of bacteria in contaminated soils and sediments.…”
Section: Acquisition and Expression Of Catabolic Genes In Plasmids Ormentioning
confidence: 99%
See 1 more Smart Citation
“…An example is the genes for the upper and lower pathways of naphthalene of several pseudomonads and sphingomonads (Yen et al, 1988), which are borne on iso-functional nah-plasmids, are often found either on different replicons or are at least organized in several transcriptional units (Stolz, 2009). Moreover, after transfer, these plasmids often undergo evident rearrangements between the various sphingomonads (Basta et al, 2005(Basta et al, , 2004Stolz, 2014). The transfer, maintenance, and recombination of these plasmids, therefore, are of great significance for the exceptional degradative capabilities of this group of bacteria in contaminated soils and sediments.…”
Section: Acquisition and Expression Of Catabolic Genes In Plasmids Ormentioning
confidence: 99%
“…The occurrence of PAH-degradative genes on mobile genetic elements may be an efficient method of spreading PAH-catabolic abilities among bacteria in polluted soils as a result of conjugative gene transfer. This makes sphingomonads capable hosts in containing several different plasmids in a single cell, an essential feature for the degradation of many organic compounds (Stolz, 2014).…”
Section: Acquisition and Expression Of Catabolic Genes In Plasmids Ormentioning
confidence: 99%
“…denitrificans cannot be excluded. The presence of catabolic genes in plasmids has been reported in numerous bacteria (Roselli et al, 2013;Stolz, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…strain KA1 (55). Until this study, Stolz (56) reported that, at most, five plasmids have been isolated from sphingomonads, namely, those found among two plasmids from Sphingomonas aromaticivorans strain F199, Sphingomonas wittichii strain RW1, and Novosphingobium pentaromativorans strain US6-1, three plasmids from S. japonicum strain UT26 and Novosphingobium sp. strain PP1Y, four plasmids from Sphingomonas xenophagum strain BN6 and Sphingobium fuliginis strain ATCC 27551, and five plasmids from Sphingomonas sp.…”
Section: Figmentioning
confidence: 98%
“…strain PP1Y, four plasmids from Sphingomonas xenophagum strain BN6 and Sphingobium fuliginis strain ATCC 27551, and five plasmids from Sphingomonas sp. strain MM-1 (56). The meaBA genes are located on plasmid pMEA02 and are surrounded by a transposable element from the IS6100 family (Fig.…”
Section: Figmentioning
confidence: 99%